Do Regulatory Focus and Mindset Affect Young Adults’ Well-Being? the Study of Individual Differences on Psychological Well-Being - Serobyan, Astghik; Song, Zheyu (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
This study investigated the relationship between regulatory focus, mindset, and well-being among young adults. Specifically, this was to examine whether promotion focus, prevention focus, and growth mindset were associated with higher levels of well-being. Our sample consisted of 332 young adults aged 18-25, who completed questionnaires assessing regulatory focus, mindset, and well-being. Results showed that promotion focus and growth mindset were positively associated with well-being, whereas prevention focus was negatively related to well-being. These findings suggest that individuals who tend to pursue positive outcomes and approach-oriented goals are more likely to experience higher levels of well-being. Overall, this study highlights the importance of considering individual differences in regulatory focus and mindset when examining the factors that contribute to young adults’ well-being.